UJI AKTIVITAS ANTIOKSIDAN VARIAN JUS DELIMA (Punicagranatum L.) DENGAN METODE FRAP - A. Muflihunna; Sukmawati Syarif; Dian Rahmawati (Fakultas Farmasi UMI, 2014)
A research test the antioxidant activity of pomegranate juice (Punicagranatum L.) with the FRAP method to measure and determine antioxidant activity. Pomegranate juice was analyzed qualitatively by using the metod FRAP with FRAP reagent. Quantitatively mix with the sample solution was analyzed by FRAP method UV-VIS Spectrophotometer at a wavelength 596 nm. By using trolox as a reference standard. From the research result that sample A and sample B sample C has antioxidant activity with an total value of antioxidant activity, sample A = 6.1243 μmol TR/g sample, sample B = 6.0913 μmolTR/g sample and sample C = 2.9651 μmolTR/g sample.Key words : Pomegranate juice, antioxidant activity, FRAP, Trolox Uv-Vis Spectrophotometer.